2011
DOI: 10.1002/pola.24790
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of π‐conjugated copolymers composed of benzo[2,1,3]thiadiazole and thiophene units bearing various alkyl groups and their application to photovoltaic cells

Abstract: π‐Conjugated polymers, PTOTBT, PTEHTBT, and PTt‐BTBT, composed of benzothiadiazole as an electron accepting unit and terthiophene as an electron donating unit in the backbone were prepared. PTOTBT, PTEHTBT, and PTt‐BTBT contained side chain groups of n‐octyl, 2‐ethylhexyl, and t‐butyl groups, respectively. Solubility, optical and thermal properties of the polymers showed strong dependences on their side chain groups. PTEHTBT having 2‐ethylhexyl groups in the side chain exhibited absorption maximum (λmax) at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…BOronDIPYrromethene (BODIPY) is an interesting chromophore with very impressive optical properties, such as very high molar extinction coefficients and fluorescence quantum yield. , Moreover, it shows good photo- and thermal stability that makes it a suitable candidate for photovoltaic applications. A well-known pathway to extend BODIPY conjugation is a Knoevenagel-like reaction that has already been used to go further in the NIR. For instance, it has been used many times to reach the therapeutic window generally targeted in medical imaging. Thiophene has also been exploited in many very efficient semiconducting conjugated polymers for applications in OLED or showing high PCEs in photovoltaics, making it an ideal unit to use in these organic polymers. , Several studies were reported using BODIPY–thiophene conjugates in small molecules or in polymer solar cells. Promising results were found there, and BODIPY-based polymers have recently shown quite high charge transport properties, but this chromophore has not proven its whole efficiency in OPV yet …”
Section: Introductionmentioning
confidence: 99%
“…BOronDIPYrromethene (BODIPY) is an interesting chromophore with very impressive optical properties, such as very high molar extinction coefficients and fluorescence quantum yield. , Moreover, it shows good photo- and thermal stability that makes it a suitable candidate for photovoltaic applications. A well-known pathway to extend BODIPY conjugation is a Knoevenagel-like reaction that has already been used to go further in the NIR. For instance, it has been used many times to reach the therapeutic window generally targeted in medical imaging. Thiophene has also been exploited in many very efficient semiconducting conjugated polymers for applications in OLED or showing high PCEs in photovoltaics, making it an ideal unit to use in these organic polymers. , Several studies were reported using BODIPY–thiophene conjugates in small molecules or in polymer solar cells. Promising results were found there, and BODIPY-based polymers have recently shown quite high charge transport properties, but this chromophore has not proven its whole efficiency in OPV yet …”
Section: Introductionmentioning
confidence: 99%
“…Both of these constituents are frequently used in the field of low gap oligomers and polymers for organic photovoltaic devices. [9][10][11][12][13][14][15] We computationally analyze the low lying excitations of these systems in detail. In agreement with other studies of similar systems 16 we find that they can be described as having, at best, ''partial'' CT character, and we compare the theoretical findings in detail to experiments.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5-Tris(dodecyloxy)benzoic acid, 4,7-bis(5-(trimethylstannyl)thiophen-2-yl)-2,1,3-benzothiadiazole, , 4,7-bis(4-hexylthiophen-2-yl)-2,1,3-benzothiadiazole (3), PCBA, PCBA-Cl, and PCBDAN were synthesized according to literature methods.…”
Section: Methodsmentioning
confidence: 99%